No, It Wasn’t About Love: Teaching Geoffrey Sax’s Othello - Johnstone, Boyda (Radical Teacher, 2022)
This Teaching Note reviews a 2001 made-for-TV film adaptation of William Shakespeare's Othello. Geoffrey Sax's production transposes the action into the streets of London where protests are erupting against racist police brutality, while the London Metropolitan Police struggles to remake its image and reestablish a sense of order. I have found that the film teaches very well alongside the play in my Introduction to Literature survey course at a public community college in New York.